Heterogeneous firm-level responses to trade liberalization: a test using stock price reactions - Breinlich, Holger (Elsevier, 2014)
This paper presents novel empirical evidence on key predictions of heterogeneous firm models by examining stock market reactions to the Canada–United States Free Trade Agreement of 1989 (CUSFTA). I derive testable predictions for a class of models based on Melitz (2003). Using the uncertainty surrounding CUSFTA's ratification, I show that the pattern of abnormal returns of Canadian manufacturing firms was strongly consistent with predictions related to export (U.S.) tariff reductions, but less so with predictions related to import (Canadian) tariff reductions. Lower Canadian tariffs did have an effect through the implied reduction in intermediate input tariffs, however.